The roots of American order - Kirk, Russell (ISI Books, 2003)
"In this now classic work, Russell Kirk describes the beliefs and institutions that have nurtured the American soul and commonwealth. Beginning with the Hebrew prophets, Kirk examines in dramatic fashion the sources of American order. His analytical narrative might be called "a tale of five cities": Jerusalem, Athens, Rome, London, and Philadelphia."--Back cover